Mitochondrial DNA involvement in frontotemporal lobar degeneration : analysis of sequence variants in MTND genes - Fernandes, Ana Sofia Cleto (2012)
Trabalho final do 6º ano, apresentado á Faculdade de Medicina da Universidade de Coimbra